A Study Of Anaemia In Pregnancy In Block Ganderbal - Vijay Mengi; Abdul Rauf; Bhan V.k (Wolters Kluwer Medknow Publications, 1988)
A cross sectional survey of Block Ganderbal to examine 544 pregnant and 100 non-pregnant women was conducted from 12 randomly selected villages. Overall 43.01% of pregnant women. Average hemoglobin level among pregnant women was 10.19 +/- 1.5 gms % with a range of 6.5 gms to 13.2 gms%. Incidence of anemia was seen to increase with increase in parity. Haemoglobin level was seen to decline with the advance of gestational age and higher hemoglobin values were observed among women taking iron and folic acid supplements than those not consuming the same.